Quality of Life of Dots Tuberculosis Patients Based on Domain Review - Widya, Pavita Arista; Yulanda, Nita Arisanti; Neri, Ervina Lili (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Pulmonary tuberculosis was a chronic and contagious disease. In 2022, the Ministry of Health identified more than 700.000 cases of tuberculosis, the highest number since the tuberculosis program became a national priority. Tuberculosis disease affected the quality of life in all aspects of life: physical, psychological, social and environmental. Low quality of life was one of the factors causing the low recovery rate of tuberculosis. The aim of this study is to analyze the quality of life in tuberculosis patients based on domain review at the DOTS-TB Polyclinic dr. Soedarso Hospital. Descriptive research with a quantitative approach and sampling using accidental sampling technique. The sample in this study amounted to 40 people and had met the inclusion criteria, namely tuberculosis patients who were undergoing treatment in the initial phase and advanced phase at the DOTS-TB Polyclinic dr. Soedarso Hospital, patients who could read in Indonesian and were willing to become respondents and follow the research stages until the end by first filling out informed consent. Statistical tests found that most respondents were in the late elderly age group (27.5%), male (62.5%), the last education was high school and college (42.5%), married (70%), working (55%) and a long history of treatment for ≤ 2 months and 3-6 months (35%). In general, patients at the DOTS-TB Polyclinic dr. Soedarso Hospital had a bad quality of life category in the domain of physical function, physical role, emotional role, energy, social function, pain and general health, while in the mental health domain most respondents had a good quality of life category. Keywords: Quality of Life, TB-DOTS and Short Form-36